Conformation-dependent recognition of mutant HTT (huntingtin) proteins by selective autophagy. Issue 12 (2nd December 2017) - Sun, Xiaoli; Fu, Yuhua; Pan, Yuyin; Lu, Boxun
ABSTRACT: Protein misfolding is the common theme for neurodegenerative disorders including Huntington disease (HD), which is mainly caused by cytotoxicity of the mutant HTT (huntingtin) protein (mHTT). The soluble mHTT has an expanded polyglutamine (polyQ) stretch that may adopt multiple conformations, among which the one recognized by the polyQ antibody 3B5H10 is the most toxic due to unknown mechanisms. In a recent study, we showed that the 3B5H10-recognized mHTT species has a slower degradation rate due to its resistance to selective macroautophagy/autophagy. In HD mouse brain tissues as well as HD patient fibroblasts and post-mortem brain tissues, the 3B5H10-recognized mHTT species lacks Lys63-polyubiquitination and SQSTM1/p62 interaction, which are essential for cargo recognition by selective autophagy. Collectively, we discovered that the mHTT protein is subject to conformation-dependent recognition by selective autophagy, which is more selective than what we perceived: the process can be selective among different conformations of the same protein, leading to conformation-dependent differences in protein degradation and toxicity.